The role of savings and wealth in southern Asia and the West (Unesco, 1963)
The following symposium is an attemp to assmble the available data for a number of countries on the economic aspect of national character and to place each peronality assement within approximately the same frame of reference to permit some preliminary comparative conclusions,...